Proyecto de factibilidad, para la creación de una empresa de construcción y remodelación de casas en el cantón Sucúa, provincia de Morona Santiago año 2016 - Unupi Uachapa, Oscar Iván (2017)
The title of this research is: "FEASIBILITY PROJECT FOR THE CREATION OF A BUILDING AND HOUSING REMODELING COMPANY IN CANTÓN SUCÚA, PROVINCE OF MORONA SANTIAGO, FOR THE YEAR 2016", aims to determine the feasibility for the creation of a company of construction and remodeling of houses "CONSTRU-REM Cía. Ltda. ", In Sucúa, in the province of Morona Santiago, in view of the fact that in this canton there is a high percentage of construction and remodeling of houses. The methodology used for this thesis project was: The analytical method, descriptive, inductive, deductive, and statistical and the techniques used were the survey of a sample of 358 families in the canton of Sucúa. Among the main results we have a projected effective demand of 1470, with a per capita use of 2 per year, an offer of 67 per year and an unsatisfied demand of 1403. With regard to the marketing plan has been established 1040 square meters of remodeling to 72.73 per square meter. In the technical study, there is an installed capacity of 1300 square meters of remodeling and a capacity used from 80% to 1040 square meters of annual remodeling. The administrative - legal study considers the organizational structure of this company, both structural and functional, in addition to describing the manual of functions for each of the required positions; The total investment required for the start-up of this company is 70% $ 34,027.00, with Ban Ecuador’s credit at 5 years term, the expected revenues for the first year will be 75,639.20 With respect to the Financial Assessment was obtained: its net present value is positive, of 12,992.30; its Internal Rate of Return is 13.75; greater than its Factorial Rate Updated 11%, Its Cost Benefit Ratio is $ 1.27 cents, earning a profit of $ 0.27 cents; Your Capital Recovery Period is 3 years 2 months and 10 days; The project is not sensitive to variations or a 15% increase in service costs, or a decrease of 10.12% in annual revenues. Regarding the environmental study, the current laws and regulations of the impact given in construction and remodeling. The success of this investment project is based on the well-structured relationship of the market, technical, administrative, organizational, financial and environmental study; the application of these studies will be the ones that will predominate in the execution of the present investment project, and finally conclusions and recommendations were determined.